Feasibility study on hydro power plant performance enhancement: Real case study - Ismail F.B.; Khaleel S.M.; Khairuddin M.A.M.; Al-Muhsen N.F.O. (American Institute of Physics Inc., 2024)
Recently, electrical power consumption has been expected to be growing within the upcoming decades driving by the high demand and rise of population. Currently, the major concern related to the used energy resources is the poor of sustainability and depletion for the fossil fuel resources which represent the main source for power generation. Therefore, the need to increase the use and optimize the renewable energy systems have become greater than ever. In Malaysia, hydro energy resources are available, and easy to be utilized. In this study, a new hydro turbine model design using SolidWorks is proposed and tested under several operating conditions. Basis of the model that this study proposed predominantly follows the existing Kaplan turbine model due to the alikeness of the operating condition and the suitability of the range in which the attained numeral fall under. Nonetheless, instillation of additional feature in the proposed model, namely the baffle plate was made to further unlock the potential of the model. Structural analysis for the selected materials comprising Stress-Strain analysis was performed. The analysis for the blade displacement and internal flow behavior for the proposed model was also included. From the tested operating conditions, theorized power output is approximately 882.9kW with runner's torque of 16733.45Nm. Analysis of the result involving the influence of fluid entry angle on turbine performance is also indicated in the form of flow trajectory, namely the density of the flow accumulated in under baffle plate feature of the model. Supporting this analysis is the simulated outcome following the simulation conducted on the model with boundary conditions obtained from earlier theoretical calculations. Numerical analysis has suggested that with 0 entry angle, average torque output appeared the highest among other entry angles. Ultimately, a safety factor of 2.246 was attained after considering stainless-steel alloy 316 as the base material. 2023 Author(s).